2009
DOI: 10.1007/s11661-009-9958-2
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Transformation and Deformation Processes and the Cyclic Stability of NiTi and NiTiCu Shape Memory Spring Actuators

Abstract: The present work addresses functional fatigue of binary NiTi and ternary NiTiCu (with 5, 7.5, and 10 at. pct Cu) shape memory (SM) spring actuators. We study how the alloy composition and processing affect the actuator stability during thermomechanical cycling. Spring lengths and temperatures were monitored and it was found that functional fatigue results in an accumulation of irreversible strain (in austenite and martensite) and in increasing martensite start temperatures. We present phenomenological equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
84
0
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(105 citation statements)
references
References 47 publications
8
84
0
11
Order By: Relevance
“…TiNi-based shape memory alloys (SMAs) have been widely used in the aerospace and biomedical fields because of their superior shape memory effect (SME), high superelasticity, and favorable biocompatibility [1][2][3][4][5]. In order to fulfill the requirement of high response frequency in the automotive and aerospace industries, TiNiCu SMAs in which Cu substitutes for Ni have been widely studied due to their narrow martensitic transformation (MT) temperature hysteresis in comparison with TiNi binary alloys [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TiNi-based shape memory alloys (SMAs) have been widely used in the aerospace and biomedical fields because of their superior shape memory effect (SME), high superelasticity, and favorable biocompatibility [1][2][3][4][5]. In order to fulfill the requirement of high response frequency in the automotive and aerospace industries, TiNiCu SMAs in which Cu substitutes for Ni have been widely studied due to their narrow martensitic transformation (MT) temperature hysteresis in comparison with TiNi binary alloys [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to design new SMAs possessing very small transformation temperature hysteresis, understanding the effect of alloying on martensite structures is of vital importance. Previously reported works have studied the effects of Cu content on transformation temperature [10], microstructure [7,8,11,12], stress-strain characteristic and fatigue life [13][14][15], as well as applications as actuators [5,16]. Earlier research has found that the Cu content in TiNiCu alloys has little influence on the MT temperature but obvious effect on the MT pathway [11,12,17].…”
Section: Introductionmentioning
confidence: 99%
“…Other important features are the hysteretic width Dh H (feature F6), widths Dh A-M (feature F8) and Dh M-A for the austenite-to-martensite and martensite-to-austenite transformations, respectively, and the open loop strain per thermal cycle, DE cycle These quantities typically depend on R bias , composition, processing history and microstructural features such as single/polycrystalline orientation/texture, precipitate morphology, dislocation substructure and internal stress (e.g. [4]). …”
Section: Introductionmentioning
confidence: 99%
“…Gil et al [14,15] showed that NiTiCu SMAs exhibit a much more narrow stress hysteresis, based on transformation stresses, as compared to binary NiTi SMAs. Fatigue testing of NiTiCu SMA actuator springs were conducted by Grossmann et al [16,17]. They reported that the functional fatigue resistance of NiTiCu SMAs is strongly improved by the addition of Cu.…”
Section: Introductionmentioning
confidence: 99%
“…Sehitoglu et al [18,19] and Biscarini et al [20] investigated the mechanical properties of NiTiCu single crystal SMAs under compression loading, and reported that the slip resistance increases when Ni-rich precipitates are present. To date, the mechanical behavior of bulk NiTiCu SMA is well established [7,[14][15][16][17][18][19][21][22][23][24]; however, few studies have focused on the effect of porosity on NiTiCu SMAs [25][26][27][28]. Goryczka et al [26,27] examined powder processing methods for producing homogenous NiTiCu SMAs.…”
Section: Introductionmentioning
confidence: 99%